Representasi Kepribadian Tokoh Ayah Pada Film Gara-Gara Warisan Karya Ernest Prakasa : Kajian Psikoanalisis Sigmuend Freud - Sitanggang, Benni; Tarigan, Della Betsya; Simatupang, Jernita; Harahap, Safinatul Hasanah (Innovative: Journal Of Social Science Research, 2024)
Literature is a picture of people's lives that occurred in the past and is influenced by the author's imagination. Literature can also be conveyed as a means of conveying ideas packaged in creative writing. This research aims to describe the personality of the father character in the film because of inheritance. This research is included in qualitative descriptive research, with the research source being films because of heritage. The data analysis technique uses the psychoanalytic approach proposed by Sigmund Freud. The film, entitled Because of Heritage, tells the story of the life of a family. The family will have accommodation but the accommodation is threatened with being sold to a drug dealer. From the results of the analysis that the author found, the father character has eight id personalities, four egos and two superegos. The conclusion in this research is that the father figure has a stubborn nature so he has quite a lot of personality ids. He is willing to make sacrifices to maintain household harmony and the welfare of his children.